2015
DOI: 10.1371/journal.pone.0116923
|View full text |Cite
|
Sign up to set email alerts
|

Functional Compartmentalization of the Human Superficial Masseter Muscle

Abstract: Some muscles have demonstrated a differential recruitment of their motor units in relation to their location and the nature of the motor task performed; this involves functional compartmentalization. There is little evidence that demonstrates the presence of a compartmentalization of the superficial masseter muscle during biting. The aim of this study was to describe the topographic distribution of the activity of the superficial masseter (SM) muscle’s motor units using high-density surface electromyography (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…In summary, we found no differences in the expression of the MyHC isoforms mRNA transcripts between the two portions of the masseter and the medial pterygoid in Pan troglodytes, indicating that the two muscles work together to elevate the mandible as has been seen in electromyography. Nevertheless, we did find slight differences between the superficial and deep portions of the masseter, perhaps related to the different functions of the portions reported in electromyographic studies in humans and other primate species (Basmajian & de Luca, 1985;Blanksma et al, 1997;Guzmán-Venegas et al, 2015).…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…In summary, we found no differences in the expression of the MyHC isoforms mRNA transcripts between the two portions of the masseter and the medial pterygoid in Pan troglodytes, indicating that the two muscles work together to elevate the mandible as has been seen in electromyography. Nevertheless, we did find slight differences between the superficial and deep portions of the masseter, perhaps related to the different functions of the portions reported in electromyographic studies in humans and other primate species (Basmajian & de Luca, 1985;Blanksma et al, 1997;Guzmán-Venegas et al, 2015).…”
Section: Discussioncontrasting
confidence: 53%
“…These findings are in line with those of Taylor and Vinyard (2013), who found that the superficial portion constituted 82.8% and the deep portion 17.2% of the total mass of the masseter. Nevertheless, functional differences between the anterior and posterior regions of the masseter observed in electromyographic studies in humans (Blanksma et al, 1997;Guzmán-Venegas et al, 2015) have not been borne out by our findings on the percentage of expression of MyHC isoforms mRNA transcripts in chimpanzees ( Table 1).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Masticatory muscles are fractionated by aponeurosis, and their internal structures vary greatly depending on the person 24 , and different local activity distributions are thought to exist within the muscles depending on the subject. Against this background, some recent studies have reported that the local activity of the masseter muscle was measured two-dimensionally using array electrodes 13 . Testa et al analyzed the local activity distribution in the masseter muscle during tooth clenching with maximum occlusal force using array electrodes arranged in 13 rows and 5 columns at 8-mm intervals, and such distribution was compared between patients with chronic neck pain and healthy subjects 12 .…”
Section: Discussionmentioning
confidence: 99%